2012
DOI: 10.1002/jctb.3882
|View full text |Cite
|
Sign up to set email alerts
|

Application of anaerobic membrane bioreactors for the treatment of protein‐containing wastewaters under saline conditions

Abstract: BACKGROUND: Anaerobic treatment of saline wastewaters may be hindered by problems related with biomass retention, since at high salt concentrations formation of biofilms and granules may not proceed well. This research studied the use of anaerobic membrane bioreactors (AnMBR) as a way to promote complete biomass retention. A lab scale AnMBR fitted with a ceramic tubular membrane was operated for 2 years. RESULTS: Results showed that enhanced biomass retention produces conditions enabling anaerobic treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This reduces the MLSS and flux encountered at the membrane potentially resulting in a lower rate of membrane fouling. Although MBR technology has been successfully employed for the treatment of non‐oily saline wastewaters, there has been very little research reported on the application of submerged MBR for the treatment of PW and these have only considered low salinity PW . According to Dores et al ., if proven successful in treating PW the opportunities for the use of MBR technology in the oil and gas industry are tremendous.…”
Section: Introductionmentioning
confidence: 99%
“…This reduces the MLSS and flux encountered at the membrane potentially resulting in a lower rate of membrane fouling. Although MBR technology has been successfully employed for the treatment of non‐oily saline wastewaters, there has been very little research reported on the application of submerged MBR for the treatment of PW and these have only considered low salinity PW . According to Dores et al ., if proven successful in treating PW the opportunities for the use of MBR technology in the oil and gas industry are tremendous.…”
Section: Introductionmentioning
confidence: 99%
“…Many industrial processes produce substantial amounts of saline wastewater (Giustinianovich et al, 2018), for which highrate treatment via anaerobic biofilm-based technologies (such as UASB reactors) are the most interesting, because of a successful biomass immobilization and retention (Xiao and Roberts, 2010;Kobayashi et al, 2018). However, high salinity is regarded a stress factor that severely hampers the performance of biological systems, negatively affecting biomass retention (Hemmelmann et al, 2013;Fang et al, 2018). In sludge granulation, granule strength and stability is considerably reduced in presence of high concentrations of Na + , leading to displacement of the bridging Ca 2+ ions within the EPS matrix (Lambert et al, 1975;Bruus et al, 1992;Ismail et al, 2010).…”
Section: Introductionmentioning
confidence: 99%